Principles of Natural Hazards Catalogs Compiling and Magnitude Classification - Varazanashvili, Otar Sh.; Gaprindashvili, George M.; Elizbarashvili, Elizbar Sh.; Basilashvili, Tsisana Z.; Amiranashvili, Avtandil G. (Journals of Georgian Geophysical Society, 2022)
A systematic inventory of natural hazard (NH) events over the Georgia is valuable for estimating expected hazard and risk, human and economic losses, quantifying the relationship between NH occurrences and climate variations and for evaluating prediction new efforts. Therefore, it is planned to compile the catalogs of the 5 types of NHs (landslide, debris ﬂow, flash ﬂood, hurricane wind and hail) causing significant economic losses and casualties in Georgia throughout the historical time, drawing upon old and new reports, scholarly articles and other hazard databases. This article develops a principles of NH data collection, the basics of magnitude classification of NH events, which will be used in the process of cataloging and magnitude harmonization of these events